Effects of Gamma Irradiation on in Vitro Cultures of Selected Orchid Hybrids - Ling, Adrain Chieng Kuang (1999)
Mutation breeding is an alternative strategy to conventional breeding. The physical mutagen, gamma (y) radiation, has long been used in various mutation breeding programmes. In this connection it is necessary to determine the optimum dose before starting any mutation breeding programme. In vitro cultured protocorm-like bodies (PLBs) of 2 orchid hybrids, Mokara Chark Kuan and Dendrobium Jacky were used to study the effects of yirradiation and to determine the optimum dose. The PLBs were irradiated with y-rays at different doses of 0, 25, 50, 75, 100, 125 and 150 Grays (Gy) in Set I and 0, 20, 40, 60 and 80 Gy in Set II of the experiment. A senes of observations on the effects of y-irradiation were recorded. Effects on genomic DNA were also observed. The present study showed that irradiation resulted in various degrees of lethality to in vitro cultures of both Mokara Chark Kuan and Dendrobium Jacky. Decrease in survival with increasing doses of y-irradiation was significantly observed. Optimum dose of y-irradiation for in vitro cultures of Mokara Chark Kuan and Dendrobium Jacky were estimated to be in the range of 20-40 Gy and 60-70 Gy respectively. Regeneration of plantlets was found to decline when higher irradiation doses were applied. Irradiation also has inhibited regeneration of in vitro cultures of both hybrids.